A Dharma Reader: Classical Indian Law, translated and edited by Patrick Olivelle. (2nd October 2019) - Smith, Caley
Abstract : A Dharma Reader: Classical Indian Law, translated and edited by Patrick Olivelle. New York: Columbia University Press, 2017. xii + 410 pp., $80.00. ISBN 978-0-23117-956-0.